PENGARUH STRES KERJA DAN MOTIVATION TO TRANSFER TERHADAP TRANSFER OF LEARNING PEGAWAI PENGADILAN AGAMA PADANG - Oga Pertissa; Yunia Wardi (Jurnal Riset Manajemen Bisnis dan Publik, 2016)
The purpose of this study was to analyze: 1) the effect of work stress on motivation to transfer, 2) Influence of motivation to transfer to transfer of learning, 3) The effect of motivation to transfer on transfer of learning, and 4) The effect of work stress on transfer of learning with mediation effect of motivation to transfer. This type of research is the study of causality. This research population is all employees of the Padang Religious Court, amounting to 60 people, and the status as civil servants who attended one training. Total samples 54 people. Data were analyzed using path analysis. The research found that: 1) Work stress significantly influence the motivation to transfer. Work stress have positive effect on motivation to transfer, 2) Motivation to transfer significantly affecting transfer of learning. Motivation to transfer will certainly increase the transfer of learning, 3) Motivation to transfer  significantly influence the transfer of learning. The better motivation to transfer will certainly increase tranfer of learning, 4) Motivation to transfer have been significantly mediated influence work stress on transfer of learning. A better motivation to transfer will increasing transfer of learning eventhough the employee having a stress in their job.  Keywords: Work stress, Motivation to transfer, Transfer of learning